Implementation of Depuration for Model Quality Assessment of Gold Ribeirão Water, Araraquara-SP (Revista Brasileira Multidisciplinar, 2010)
Mathematical models used to simulate the quality and the process of self-purification of water bodies are important tools to aid the management of water resources. The main objective of this paper was to apply a mathematical model (QUAL-UFMG) to evaluate the water quality of the stream “ribeirão do Ouro", Araraquara (SP). Based on the profiles of dissolved oxygen (DO) and of the biochemical oxygen demand (BOD5,20) obtained along the longitudinal section of the river, it was possible to determine the areas of self-purification and to verify compliance with the standards of water quality established by Resolution CONAMA 357/2005. The model and the obtained results will be able to support managers and researchers in the prevention, control and studies related to pollution of this water body.
Keywords: Mathematical Modeling; Surface water quality; Water resources management; Model QUALUFMG